Understanding Men's Engagement and Disengagement When Seeking Support for Mental Health. Issue 2 (March 2023) - Kwon, Minjoo; Lawn, Sharon; Kaine, Christine
Men are less likely to utilize health care services compared with women. When it comes to mental health, men have been reported to hold more reluctant attitudes toward engaging with mental health services. Current studies have predominantly been quantitative and focused on understanding effective strategies to promote men's engagement and why men may avoid help-seeking or may not seek help early; few studies exist of men's disengagement from services. Much of this research has been undertaken from the services' perspective. The study reported here attempts to gain better insight into the reasons men give for their disengagement from mental health services and what men say will reengage them back into the system. This research was a secondary analysis of data collected by a national survey conducted by Lived Experience Australia (LEA). Responses of 73 male consumers were gathered and analyzed. Analysis of the responses was split into two themes with associated subthemes: (1) Why men disengage : (1.1) Autonomy; (1.2) Professionalism; (1.3) Authenticity; and (1.4) Systemic Barriers; and (2) What will help men reengage : (2.1) Clinician-driven reconciliation, (2.2) Community and Peer Workers; and (2.3) Ease of reentry. Findings highlight strategies to prevent disengagement such as creating open and honest therapeutic environments and improving men's mental health literacy while providing care. Evidence-based approaches to reengage male consumers are suggested along with an emphasis on men's strong preferences for community-based mental health services and peer workers.